Literature review on the role of artificial intelligence in identifying and developing the potential of secondary school students for excellent character building - Darda Abdullah Sjam; Cep Miftah Khoerudin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The development of artificial intelligence (AI) has changed the direction of modern education towards more adaptive, reflective, and learner-centred learning. This study aims to analyse the role of AI in identifying and developing student potential, as well as its contribution to the formation of excellent character in the digital age. This research is a narrative literature review that examines various relevant scientific publications published between 2018 and 2025, sourced from international databases such as Scopus, ERIC, and ScienceDirect, as well as SINTA-indexed national journals. The literature selection process was carried out using thematic criteria that emphasised the suitability of the context of primary, secondary, and higher education in Indonesia. Data analysis was conducted using a thematic-inductive approach to identify patterns of relationships between AI implementation, learning potential development, and moral character formation. The results showed that AI plays a role in facilitating personalised learning, increasing student engagement and motivation, and fostering empathy and responsibility through adaptive feedback and reflective interaction. On the other hand, challenges arise in terms of ethics, data privacy, and the digital divide. This study emphasises that AI implementation must be oriented towards human values so that technology functions as a pedagogical partner in shaping an intelligent and characterful generation.